1978
DOI: 10.1080/00362177885380381
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasma capsulatum: Chemical variability of the yeast cell wall

Abstract: Four strains of HistopIasma capsulatum were analyzed to observe any variations in their cell wall composition. Strair~ G-184B produced the same amount of sugars reported by Domer (2) although qualitative analyses agreed with Kanetsuna's report (4) as far as the presence of glucose, galaetose, and mannose was concerned. Our results agree with previous reports in classifying H. capsutatum into chemotypes I and II, the latter having more ~-glucan in its cell wall. A decrease in the amount of fraction 2 (e-glucan)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The distinct chemotypes were later confirmed by Reiss (95) The spontaneous disappearance of a virulence-associated phenotype during culture has many precedents among pathogenic organisms, and phase variation is a common theme linked with adaptation of different environments (both outside and inside of hosts). Culture-associated loss of ot-(1,3)-glucan had been seen previously during extended in vitro passage of H. capsulatum (99), and this loss probably was due to the progressive accumulation of smooth variants in cultures being transferred without single-colony cloning.…”
Section: Spontaneous Avirulent Variantssupporting
confidence: 52%
“…The distinct chemotypes were later confirmed by Reiss (95) The spontaneous disappearance of a virulence-associated phenotype during culture has many precedents among pathogenic organisms, and phase variation is a common theme linked with adaptation of different environments (both outside and inside of hosts). Culture-associated loss of ot-(1,3)-glucan had been seen previously during extended in vitro passage of H. capsulatum (99), and this loss probably was due to the progressive accumulation of smooth variants in cultures being transferred without single-colony cloning.…”
Section: Spontaneous Avirulent Variantssupporting
confidence: 52%
“…We further sought to verify the decrease of α‐(1,3)‐glucan in the amy1 ‐null strain with a biochemical analysis of cell wall polysaccharide composition. Chemical and ultrastructural studies on the cell wall of H. capsulatum yeast have shown that the alkali‐soluble, precipitable fraction is composed of > 99% glucose with α‐(1,3)‐linkages (Kanetsuna et al ., 1974; San‐Blas et al ., 1978). Yeast cell wall polysaccharides were fractionated based on their distinct alkali solubilities and the fraction containing α‐(1,3)‐glucan was examined for its glucose content using standard colorimetric sugar detection techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In strain G-184A, Domer (47) and San-Bias et al (147) reported the presence of 47-48% hexoses, whereas Kanetsuna et at. (76) reported as much as 82% for the same strain.…”
Section: Histoplasma Capsulaturnmentioning
confidence: 94%